(3eNGWQ GdEYJeGO Ydi GdHjGfGJ GdeMGSHjI YfO Jbjjec ddESJKeGQGJ aj Shb GdChQGb GdeGdjIs - (3eMeO eMehO YHO QHg(B, (3eMeOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3GdESJKeGQGJ aj GdChQGb GdeGdjI heNGWQgG(B- (3GJaGbjI JMQjQ GdNOeGJ GdeGdjI hGdeUQajI hJCKjQgG Ydi GdShb GdGhQGb GdeGdjI aj eUQ(B- (3eNGWQ GdEYJeGO Ydi GdHjGfGJ GdeMGSHjI YfO Jbjje GdESJKeGQGJ aj Shb GdeGdjI aj eUQ(B- (3eYGjjQ Jbjje GdESJKeGQGJ aj Shb GdGhQGb GdeGdjI(B.s
Keywords: (3GdChQGb GdeGdjIs; (3GdESJKeGQGJs; (3GdHhQUIs